Fertility preservation and assisted reproductive strategies in endometrial cancer patients with lynch syndrome - Liu, Junhan; Zheng, Ying; Liu, Jianhong (Frontiers in Oncology, 2025)
Patients with LS-EC can be treated with progestin-based fertility-sparing treatment under close monitoring, and pregnancy is recommended as soon as possible after complete remission (CR) of the disease, with assisted reproduction, supplemented by PGT-M, to minimize the probability of inheritance of the disease in the offspring. Radical surgery for endometrial cancer is recommended as soon as possible after completion of childbearing to minimize recurrence. The role of assisted reproductive technologies (ART) and preimplantation genetic testing for monogenic disorders (PGT-M) was explored. For patients achieving CR, early initiation of ART, especially IVF with frozen-thawed embryo transfer (FET), was associated with improved reproductive outcomes. PGT-M proved valuable in preventing the transmission of pathogenic MMR variants to offspring. Early use of ART and integration of PGT-M are critical for maximizing reproductive success while minimizing oncologic and hereditary risks.